Juan Arambula for Fresno School Board Election Night at Finn McCouls - Watkins, Howard::::::::: (1987)
Adults: Amy Arambula, Juan Arambula; Children: Diego Arambula, Miguel Arambula, Joaquin Arambula, Carmen Arambula and niece Anita Arambula